Sensory Eye Dominance in Treated Anisometropic Amblyopia - Yao Chen; Jiafeng Wang; Hongmei Shi; Xiaoxiao Wang; Lixia Feng (Neural Plasticity)
Amblyopia results from inadequate visual experience during the critical period of visual development. Abnormal binocular interactions are believed to play a critical role in amblyopia. These binocular deficits can often be resolved, owing to the residual visual plasticity in amblyopes. In this study, we quantitatively measured the sensory eye dominance in treated anisometropic amblyopes to determine whether they had fully recovered. Fourteen treated anisometropic amblyopes with normal or corrected to normal visual acuity participated, and their sensory eye dominance was assessed by using a binocular phase combination paradigm. We found that the two eyes were unequal in binocular combination in most (11 out of 14) of our treated anisometropic amblyopes, but none of the controls. We concluded that the treated anisometropic amblyopes, even those with a normal range of visual acuity, exhibited abnormal binocular processing. Our results thus suggest that there is potential for improvement in treated anisometropic amblyopes that may further enhance their binocular visual functioning.